A multimode-interferenced electrooptic TE/TM mode splitter - Kim, G.; Kang, B.; Lee, S.; Chang, H.; Choi, M.; Lee, S.; Woo, D.; Kim, S. (CLEO/Pacific Rim 1999 - Pacific Rim Conference on Lasers and Electro-Optics, 1999)
TE/TM mode splitting is an important integrated-optic function for fiber communication system and fiber sensors, where orthogonal polarization states of the signals are particularly emphasized. Guided-wave TE/TM mode splitting has been demonstrated in LiNbO3, III-V compound semiconductors and polymers. They used an asymmetric Y-junction with different preferences of polarizations, a double mode waveguide with different coupling lengths for TE and TM modes, and the photo-bleaching induced birefringence, respectively. We present a novel TE/TM mode splitter utilizing the multimode interference and the linear electrooptic (LEG) effect, It employs a new operating principle, and shows several important characteristics: high extinction ratio, low excess loss, easy fabrication and large fabrication tolerance, and integratibility with other photonic devices. ？ 1999 IEEE.